Geopolitical position and defence of Spain’s national interests: rethinking the question of the Perejil small island twenty years later - DÍAZ GALÁN, Elena Carolina (Journal of the Spanish Institute for Strategic Studies, 2023)
The definition of Spain’s geopolitical position on the international order is one of the fields that still needs to be explored. The situation of dependence of our country in matters of security and defense by its membership to international organizations, such as NATO and the European Union, is not a obstacle to Spain in order to have singular postulates in its foreign policy. The determination and defense of Spain’s national and vital interests would be at the base of the place that Spain should occupy in world geopolitics. It is possible to clarify this issue by analysing the decisions taken 20 years ago in the Perejil small island. This case embodies some of the components that must shape substantial aspects of the foreign policy of any State. This work aims to clear of the main postulates that outline the defense of the most fundamental interests by Spain, reflecting on territorial sovereignty and the use of force in international relations.